2018
DOI: 10.7573/dic.212524
|View full text |Cite
|
Sign up to set email alerts
|

Administration of intravenous morphine for acute pain in the emergency department inflicts an economic burden in Europe

Abstract: BackgroundAcute pain is among the leading causes of referral to the emergency department (ED) in industrialized countries. Its management mainly depends on intensity. Moderate-to-severe pain is treated with intravenous (IV) administered opioids, of which morphine is the most commonly used in the ED. We have estimated the burden of IV administration of morphine in the five key European countries (EU5) using a micro-costing approach.ScopeA structured literature review was conducted to identify clinical guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The choice of two comparators for the treatment of moderate pain reflects the heterogeneity of treatment available in the country and also allows for a therapeutic alternative in the event that the patient is allergic to paracetamol or NSAIDs. These treatments are commonly implemented in pain management guidelines [ 11 , 14 ] and have been shown to be effective options for the management of moderate-to-severe musculoskeletal pain [ 31 33 ]. The definitive SoC in Italy will allow for a clear and consistent comparative treatment arm, while the co-primary objective will allow a separate comparison of methoxyflurane versus IV paracetamol/ketoprofen for moderate pain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of two comparators for the treatment of moderate pain reflects the heterogeneity of treatment available in the country and also allows for a therapeutic alternative in the event that the patient is allergic to paracetamol or NSAIDs. These treatments are commonly implemented in pain management guidelines [ 11 , 14 ] and have been shown to be effective options for the management of moderate-to-severe musculoskeletal pain [ 31 33 ]. The definitive SoC in Italy will allow for a clear and consistent comparative treatment arm, while the co-primary objective will allow a separate comparison of methoxyflurane versus IV paracetamol/ketoprofen for moderate pain.…”
Section: Methodsmentioning
confidence: 99%
“…Opioids are a highly effective treatment option for severe pain, but require additional resources for prescribing, administration, monitoring and observation due to their controlled status and challenging safety profile. A recent review has estimated the cost per patient of intravenous (IV) morphine administration in Europe at €18–28 (of which €14–22 is accounted for by workforce costs), rising to €121–132 when morphine-related adverse events (AEs) and IV-related complications are also considered [ 14 ]. Furthermore, there is often a general reluctance on the part of healthcare providers to prescribe opioids due to concerns over safety, dependence and abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Patients administered opioids require safety monitoring due to the risk of sideeffects such as respiratory depression, cardiovascular events, nausea and vomiting, which together with initial placement of an IV catheter, incurs considerable time and resource costs. 9 Opioid analgesics are controlled medications and there may be reluctance among health-care professionals and patients to use opioids due to regulatory barriers in prescription and concerns about misuse and abuse. 7 Intranasal opioid analgesia is less invasive but is not suitable for patients with facial trauma.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] In a study done in four regional cancer centers in India, a total of 88% of patients reported experiencing pain for about 7 days, and approximately 60% reported that their worst pain was severe. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%